Corporate social responsibility and financial performance: an analysis of companies listed on B3 - Pinheiro, Livia Bruna Gois (2023)
This research aimed to analyze how financial performance influences Corporate Social Responsibility in companies in Brazil. Data was collected on financial information, as well as information on Corporate Social Responsibility, for the period between 2010 and 2019, from companies listed on the Brazilian Stock Exchange. For data collection, the Economatica® data system was used to obtain information on financial and control performance. With regard to Corporate Social Responsibility, the CSRHub database was used. Statistical techniques were then used to analyze the data, such as correlation analysis and ordinary least squares multiple linear regression. The results showed the relevance of financial performance in corporate social responsibility practices, which may vary depending on the social practice applied by the organizations. Financial performance showed an influence on the four Corporate Social Responsibility practices investigated: community, environment, governance and employees. In this sense, this research sought to broaden understandings about improving company management by analyzing the evidence linking financial performance to Corporate Social Responsibility practices. The relevance of this study lies in providing concrete evidence of the impact of financial performance on Corporate Social Responsibility initiatives, thus contributing to the overall improvement of business management.